Güncel Hemşirelik Çalışmaları VII (Bahar) - Kartal Günen, Hilal; Göktaş, Sonay; Öçal , Gülnadiye; Akduran, Funda; Yıldırım Gökşen, Dicle Filiz; Uludağ, Elif; Bozkul, Gamze; Altun Uğraş, Gülay; Yılmaz Koçak, Mine; Atçeken, Hanife; Uzunalioğlu, Miyase; Gezginci, Elif; et al. (Academician Publishing Book DOI Portal, 2024)
-